2018
DOI: 10.1080/20009666.2018.1487244
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement intervention to enhance performance and perceived confidence of new internal medicine residents

Abstract: Background: Orientation for new medical residents is challenging due to the diversity of prior experiences and cultural backgrounds and is compounded by a lack of orientation curricula that adequately addresses the needs of the medical residents to allow them to perform their duties in an efficient manner from the start. The beginning of residency training is associated with reduced quality of healthcare widely referred to as the ‘July effect’.Objective: To assess the impact of a peer-led orientation for new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Indeed, the complexity of prescribing takes time to master, including determining priorities in a time-pressured medical environment. However, positive experiences from peer-led orientation for new interns have been described elsewhere [20], suggesting that time for interaction with colleagues may add value, irrespective of seniority.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the complexity of prescribing takes time to master, including determining priorities in a time-pressured medical environment. However, positive experiences from peer-led orientation for new interns have been described elsewhere [20], suggesting that time for interaction with colleagues may add value, irrespective of seniority.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, active learning has been shown favorable among students [19], a finding which may also apply to post-graduate training. The small group format may facilitate discussions, and interaction between knowledgeable tutors and participants has been shown to increase the comfort of the group and their performance regarding the topics focused on [13,18,20]. Interestingly, a recent educational effort using small-group educational workshops with peers increased evidence-based practice among the participating health professionals [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Techniques employed have ranged from the provision of one-off and regular teaching sessions to clinicians through to programmes providing both teaching and feedback. [19][20][21][22][23] Importantly, it has been shown that the results of these QIPs can be long-lasting. 24 Additionally, the Royal College of Physicians has provided guidance on how to improve discharge summaries, which can be utilised when designing teaching on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 5 ] investigated the use of medical record templates in an EMR system, and the result showed that residents appreciate templates, but the overall documentation quality remained unknown. Other studies have developed curricula for better understanding of medical documentation [ 6 , 7 , 9 , 10 ]. However, these curricula and study results are insufficient for use with medical record writing assessment.…”
Section: Introductionmentioning
confidence: 99%